MENGGUNAKAN GRAMMARLY UNTUK MENINGKATKAN KUALITAS MENULIS SISWA SMP KELAS 9 - Widya Ayu Kusuma; Fauris Zuhri (ELTIN Journal, 2025)
As writing proficiency is essential for academic success, integrating technology such as Grammarly has gained attention as a potential tool for improving students’ writing skills. This study investigates the impact of using Grammarly to enhance the writing quality of ninth-grade Junior High School students. This study used a pre-experimental design at a private junior high school in Sidoarjo. The sample included ICO ninth-grade students.  The study used an essay writing test (pretest and posttest) as its research instrument. Since the normality test indicated non-normal data distribution, the Wilcoxon Rank Test was used to compare pretest and posttest scores. The Wilcoxon test yielded a two-tailed Asymp. Sig result of 0.000. Since this value is lower than 0.05, the findings support the hypothesis that Grammarly enhances students' writing quality. The findings from this study reveal a general improvement in students' writing skills across all five evaluated aspects: Content, Organization, Vocabulary, Language Use, and Mechanics. This research also provides recommendations for teachers and students to consider integrating technology such as Grammarly in teaching writing to achieve better learning outcomes.